The effectiveness of IMB Services at the Makassar City Investment Office and One Door Integrated Services at Makassar City - Mirdawati Mirdawati; Jamaluddin Jamaluddin; Risma Niswaty; Muhammad Darwis; Rudi Salam (Program Pascasarjana Universitas Negeri Makassar, 2018)
This study aims to determine the effectiveness of Building Permit (IMB) service at the Office of Investment and Integrated Services One Door Makassar City. This study is a qualitative descriptive research that in the process of collecting data using observation techniques, interviews, and documentation. Based on the result of the research indicates that the effectiveness of building permit service at the Office of Capital Investment and Integrated Service One Door of Makassar City is quite effective with the description (1) simplicity is quite effective, (2) clarity is effective, (3) Legal certainty is not effective, 4) Accuracy is effective, (5) security is effective, (6) Responsibility is quite effective, (7) Completeness of Facilities and Infrastructure quite effective, (8) Ease of Access has been effective, (9) Discipline, Courtesy and Friendliness have been effective , and (10) Convenience is quite effective.